Unequal Bandpass Filtering Power Divider Based on Hybrid HMSIW-SSPP Modes - Pan, Bai Cao; Yu, Ping; Guo, Ben Jian; Qian, Ya Hui; Luo, Guo Qing (Frontiers in Physics, 2022)
This letter presents a novel unequal bandpass filtering power divider based on hybrid-mode of half mode substrate integrated waveguide (HMSIW) and spoof surface plasmon polaritons (SSPPs). Bandpass response is achieved by combining the transmission properties of HMSIW and SSPPs simultaneously. The operating bandwidth can be designed in a wide range by simply optimizing the dimensions of HMSIW and SSPPs. In addition, defected ground structures (DGSs) are etched on the bottom of the substrate to improve out-of-band suppression. The power division ratio of the proposed unequal power divider is finally optimized to 1:3. The measured results agree with the simulated one. Such design provides a stable power division within wide frequency range from 6.5 GHz to 9.5 GHz.